Oxygen reduction at electrodeposited ZnO layers in alkaline solution. (10th November 2016) - Prestat, M.; Vucko, F.; Lescop, B.; Rioual, S.; Peltier, F.; Thierry, D.
Abstract: Zinc oxide (ZnO) layers were electrodeposited from an aqueous nitrate bath at 62 °C on copper substrates. At −0.9 V (vs. saturated calomel reference electrode), the growth rate is 600 nm min −1 . In the early stages of the deposition, the layers are porous. At longer deposition times, the surface becomes dense and rough. The wurtzite crystalline structure is confirmed by XRD measurements and the chemical composition of the ZnO surface was assessed by EDX and XPS. The oxygen reduction reaction (ORR) was investigated at room temperature in a 10 −3  M KOH solution with KCl as supporting electrolyte. The ORR onset potential is found to be much larger than that of platinum taken as reference electrocatalyst. Rotating ring-disk electrode experiments evidence a negligible production of hydrogen peroxide as intermediate product of the reaction. The latter follows thus a direct four-electron pathway at pH ∼11.